EFECTIVENESS OF VIRUS MATERIAL TOPIC STUDENT WORKSHEET BASED ON KNOW-LEARNED (K-L) METACOGNITIVE STRATEGY TO TRAIN STUDENT METACOGNITIVE SKILLS - Sonia Savitri; Endang Susantini (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2019)
Metacognitive skill is essential for students. One of learning materials which can train metacognitive skillis  worksheet  based  on  metacognitive  strategy.  This  research  aimed  to  produce  an  effective  studentworksheet based on Know-Learned (K-L) strategy on virus material topic to train student’s metacognitiveskill.  This  research  which  had  been  held  in  Biology  Department,  FMIPA,  Unesa.  This  study  was  adevelopmental  research  which  referred  to  3-D  model  namely  define,  design,  and  develop.  The  researchstage  started  with  define  stage  which  conducted  by  analyzing  curriculum  on  virus  material.  Thencontinued  with  design  stage  which  conducted  by  designing  and  developing  student  worksheet.  Studentworksheet consists of know-learned phase, which equipped with self-confidence level column, comparingconcept  column,  and  score  column,  so  it  can  facilitate  students  to  practice  monitoring  and  evaluationskills.  Then  at  the  develop  stage,  student  worksheet  implemented  limitedly  to  fifteen  10thgrade  studentsof  SMAN  4  Sidoarjo.  Finally,  the  effectiveness  of  student  worksheet  evaluated  based  on  studentmetacognitive  skill,  completeness  of  indicators,  and  gain  score.  The  research  result  showed  that  thestudent  worksheet  was  effective  with  the  student’s  metacognitive  score  of  3.93  (very  good  category)  andpositive  sensitivity  in  the  range  of  0.3-1.0.  In  addition,  student  worksheet  was  also  effective  to  gainlearning  outcomes  of  93.33%  students  with  the  high  criteria  and  6.67%  student  with  the  medium  criteria.Therefore,  student  worksheet  based  on  K-L  metacognitive  strategy  was  effective  to  train  studentsmetacognitive skill and gain their learning outcomes at once on virus material.Keywords: worksheet, know-learned, metacognitive skill, virus material.